Curriculum Management for Character Education in a Non-Formal School: A SWOT-Based Case Study at Gajahwong School, Yogyakarta - Nur Sabrina Sorfina; Hidayati, Wiji (Journal of Islamic Education Management Research, 2025)
Purpose – This study investigates the curriculum management process for character education at Gajahwong School, a non-formal educational institution in Yogyakarta, Indonesia. It aims to identify internal and external factors affecting curriculum implementation and to develop strategies for enhancing moral education through SWOT analysis. Design/methods – The research employed a descriptive qualitative method, drawing on observations, structured interviews, and document analysis to examine planning, organizing, implementation, and evaluation processes. Three key informants were selected purposively: a school coordinator, a class educator, and a parent. The Internal and External Strategic Factors Analysis Summaries (IFAS and EFAS) were used to construct a SWOT matrix and formulate strategic responses. Findings – Curriculum management at Gajahwong School is participatory and value-driven, emphasizing socio-emotional learning, local cultural integration, and child-centered pedagogy. Key strengths include flexible curriculum design, structured planning, and volunteer commitment. However, challenges persist, such as lack of alignment with national standards, insufficient infrastructure, and limited continuity of educators. The SWOT matrix revealed a strategic position that favors opportunity-driven growth, suggesting the potential for expansion through digital branding, inclusive education, and community partnerships. Research implications/limitations – The contextual specificity and reliance on qualitative data may limit generalizability. Additionally, the absence of a standardized evaluation framework and dependence on informal volunteer systems present challenges for scalability. Future studies should include longitudinal and comparative research across non-formal settings and investigate hybrid curricular models. Practical implications – The findings provide actionable insights for policymakers, curriculum developers, and educational practitioners seeking to institutionalize character education in marginalized communities. They highlight the importance of integrating moral values, local wisdom, and emotional development into non-formal learning systems. Originality/value – This study contributes to the limited literature on curriculum management in informal educational contexts and introduces a SWOT-based framework for enhancing character education. It demonstrates how culturally rooted, community-led institutions like Gajahwong can offer innovative models of child development beyond conventional schooling paradigms.